The Effects Of Additional Runways And Taxiways On The Workload Of Soekarno-Hatta Tower North Personnel At AirNav JATSC - Dwi Lestary; Hibatullah; Pangsa Rizkina Aswia; Yanur Jinu Satiti (Politeknik Penerbangan Makassar, 2022)
This study aims to analyze the effects of additional runways and taxiways on the workload of Soekarno-Hatta Tower North Personnel. Does the 07L-25R runway condition with the current condition affect the ATC workload. The research method used is a quantitative method. The research instrument uses the NASA TLX calculation method, questionnaire and documentation study which aims to obtain data followed by testing to find out whether there is an influence between the two variables. Based on the analysis of the research data, it is concluded that the additional of new runways and taxiways currently has an influence on the ATC workload so it needs adjustments to runway operations based on related literature studies. Keywords : aerodrome control tower; workload; runway